Museums and Technologies of Presence (Taylor & Francis, 2024)
and, Lambert, Maria, Museums, of, Presence, Shehade, Stylianou, Technologies, Theopisti
English
Keywords: Library & information services; Museology & heritage studies; and, Lambert, Maria, Museums, of, Presence, Shehade, Stylianou, Technologies, Theopisti